EFFECTIVENESS OF CRYOTHERAPY FOLLOWED BY MUSCLE ENERGY TECHNIQUE IN POST OPERATIVE KNEE STIFFNESS PATIENT - Shruti kumbhar; Dr. G. Varadharajulu (The Bioscan, 2025)
Introduction: Post-Operative knee stiffness is a common condition after any specific knee surgery. In this condition there is stiffness of knee joint causes pain, reduced knee range of motion and its affect on quality of life of individual. There are various therapeutic options available for the condition like stretching exercise, isometric exercise, strengthening exercise. Another therapeutic option is cryotherapy which is effective to reduce pain, inflammation. Manual therapies like muscle energy technique help to restore joint range of motion. Methodology: Interventional study conducted on 30 post-operative knee stiffness patients, participants age ranged from 20-40 yrs with all genders included in this study. Conventional physiotherapy intervention applied on 15 participants that was group A, which include hot moist pack , isometric exercise, strengthening exercise, and stretching exercise and group B was recived conventional physiotherapy along with muscle energy technique followed by icing which was experimental group and 15 participants included in group B, all participants were evaluated by pre and post treatment by Visual analogue scale (VAS) to calculate pain intensity , Lower extremity functional scale (LEFS) to measure quality of life of individual, universal goniometer to measure range of motion of joint. Result: This study showed that, the post-treatment results showed significantly better outcomes in the group B. Pain levels (VAS) reduced to (4.2 ± 1.08) in group B compared to group A (5.39 ± 1.16) (p < 0.001). Functional improvement (LEFS) was greater in the group B (65.13 ± 7.76) than in the group A (41.2 ± 7.61, p < 0.001). Flexion range increased to (102.47° ± 12.38°) in group B than (77.67° ± 13.23°) in group A, and extension improved to (1.73° ± 1.10°) in group B than (3.67° ± 1.84°) in group A (p = 0.002). Conclusion: The study concludes that the experimental group receiving Muscle Energy Technique followed by icing showed significantly better outcomes than the conventional group. Pain levels were lower, functional ability improved, and range of motion increased in both flexion and extension. These results suggest the experimental approach is more effective for managing post-operative knee stiffness.